1976
DOI: 10.2337/diab.25.7.586
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Response to Oral Glucose in Patients with a Previous Myocardial Infarction and in Patients with Peripheral Vascular Disease: Hyperinsulinism and Its Relationships to Hypertriglyceridemia and Overweight

Abstract: The insulin response to an oral glucose load (100 gm.) in 127 patients with a previous myocardial infarction (MI) (six months to one year) and in 65 patients with surgically treated or arteriographically identified peripheral vascular disease (PVD) was compared with that of 89 controls after matching the three collectives for age, glucose tolerance, and per cent ideal body weight (% IBW). The insulin response was of greater magnitude in MI and PVD groups than in respective control groups also in the absence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
1

Year Published

1977
1977
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 2 publications
3
10
1
Order By: Relevance
“…Although an abnormality in glucose tolerance may occur in the majority of patients who have had a myocardial infarction (3,6,16,17), an increased insulin response to glucose administration has been reported to have an even higher incidence in such patients (14,18,19). But the present study suggests that if the delay in the glucose peak in the G.T.T.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Although an abnormality in glucose tolerance may occur in the majority of patients who have had a myocardial infarction (3,6,16,17), an increased insulin response to glucose administration has been reported to have an even higher incidence in such patients (14,18,19). But the present study suggests that if the delay in the glucose peak in the G.T.T.…”
Section: Discussioncontrasting
confidence: 56%
“…To obtain the mean correlation coefficient, the correlation coefficients (r) for the patient and control samples were compared and combined using the Fisher z transformation (13 (14), the one obese patient was considered separately, leaving 10 patients in Group II. The G.T.T.…”
mentioning
confidence: 99%
“…Individuals who suffered a myocardial infarction had a higher I/G ratio than controls [21]. Santen et al observed a higher fasting I/G ratio in diabetic patients with atherosclerosis compared with those without atherosclerosis [22].…”
Section: Then: Insulin-a Link Between Metabolism and Cardiovascular Cmentioning
confidence: 98%
“…Interference from previous antihypertensive treatment also seems unlikely because, firstly, all patients were off-treatment from at least 2 weeks at the moment of sampling, and, secondly, all had previously been treated with angiotensin-converting enzyme inhibitors and calcium-channel blockers; both classes of drugs did not change insulin sensitivity nor circulating insulin in previous reports. [26][27][28] A second noteworthy finding is confirmation that PVD patients exhibit hyperinsulinaemia and marginally elevated plasma glucose in response to oral glucose, 12,13 as well as a high prevalence of triglyceride abnormalities, 29 both suggestive of reduced insulin sensitivity. 24 A new finding is that hyperinsulinaemia cannot be ascribed to hypertension, since the same metabolic abnormality was shared by strictly normotensive and hypertensive subjects; possibly, physical deconditioning due to disease status may be a relevant factor.…”
Section: Lack Of a Relationship Between Urine Albumin And Post-load Pmentioning
confidence: 95%
“…For this reason, those same parameters were also evaluated in normotensive patients with atherosclerotic peripheral vascular disease (PVD) in whom hyperinsulinaemia could be anticipated on the basis of previous reports. 11,12 …”
Section: Introductionmentioning
confidence: 99%